The Effect of Auditor Skills, Forensic Auditing, and Auditor Professionalism on Fraud Detection - Muhammad Rafid Muzhaffar; Khomsiyah Khomsiyah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine whether the influence of Auditor Expertise, Forensic Audit, and Auditor Professionalism on Fraud Detection at the Public Accounting Firm. The type of research used in the study is Quantitative, with primary data sources that are data obtained directly without intermediaries by distributing questionnaires. The population of this study were auditors who worked at the Public Accounting Firm in the DKI Jakarta area. The sample was determined based on the survey method, so that the total respondents in this study was 119 respondents. Hypothesis testing using partial test (t-test) and simultaneous test (F-test). The test results prove that: Auditor Expertise, Forensic Audit, and Auditor Professionalism have a positive effect on Fraud Detection.